Zwitterionic materials for antifouling membrane surface construction. (August 2016) - He, Mingrui; Gao, Kang; Zhou, Linjie; Jiao, Zhiwei; Wu, Mengyuan; Cao, Jialin; You, Xinda; Cai, Ziyi; Su, Yanlei; Jiang, Zhongyi
Graphical abstract: Abstract: Membrane separation processes are often perplexed by severe and ubiquitous membrane fouling. Zwitterionic materials, keeping electric neutrality with equivalent positive and negative charged groups, are well known for their superior antifouling properties and have been broadly utilized to construct antifouling surfaces for medical devices, biosensors and marine coatings applications. In recent years, zwitterionic materials have been more and more frequently utilized for constructing antifouling membrane surfaces. In this review, the antifouling mechanisms of zwitterionic materials as well as their biomimetic prototypes in cell membranes will be discussed, followed by the survey of common approaches to incorporate zwitterionic materials onto membrane surfaces including surface grafting, surface segregation, biomimetic adhesion, surface coating and so on. The potential applications of these antifouling membranes are also embedded. Finally, we will present a brief perspective on the future development of zwitterionic materials modified antifouling membranes. Statement of Significance: Membrane fouling is a severe problem hampering the application of membrane separation technology. The properties of membrane surfaces play a critical role in membrane fouling and antifouling behavior/performance. Antifouling membrane surface construction has evolved as a hot research issue for the development of membrane processes. Zwitterionic modification of membrane surfaces has been recognized as an effective strategy to resist membrane fouling. This review summarizes the antifouling mechanisms of zwitterionic materials inspired by cell membranes as well as the popular approaches to incorporate them onto membrane surfaces. It can help form a comprehensive knowledge about the principles and methods of modifying membrane surfaces with zwitterionic materials. Finally, we propose the possible future research directions of zwitterionic materials modified antifouling membranes.